Notes on helminth parasites of tuna fishes (Scombridae) in Brazil Notas sobre los helmintos parásitos del atún (Scombridae) en Brasil - Márcia Cristina Nascimento-Justo; Anna Kohn (Revista Mexicana de Biodiversidad, 2012)
Four species of Scombridae from the coast of Rio de Janeiro, southwest Atlantic Ocean were found to be parasitized with species of Didymozoidae (Digenea): Thunnus atlanticus (Lesson) a new host record for Nephrodidymotrema ahi Yamaguti, 1970, Didymocystis neothunni (Yamaguti, 1970), and Didymozoon longicolle (Yamaguti, 1970); Thunnus obesus (Lowe) parasitized by Didymozoon longicolle and reported as a new host for Nephrodidymotrema ahi; Thunnus albacares (Bonaterre) parasitized by Nephrodidymotrema ahi, and Katsuwonus pelamis (Linnaeus) by Didymozoon longicolle. Measurements, figures, and parameters of infection are presented. Cuatro especies de Scombridae de la costa de Río de Janeiro, suroeste del océano Atlántico, se reportan parasitados con diferentes especies de Didymozoidae (Digenea): Thunnus atlanticus (Lesson) un registro de nuevo huésped para Nephrodidymotrema ahi Yamaguti, 1970, Didymocystis neothunni (Yamaguti, 1970) y para Didymozoon longicolle (Yamaguti, 1970); Thunnus obesus (Lowe) parasitado por Didymozoon longicolle, se indica como nuevo huésped para Nephrodidymotrema ahi; Thunnus albacares (Bonaterre) parasitados por Nephrodidymotrema ahi y Katsuwonus pelamis (Linnaeus) por Didymozoon longicolle. Se presentan las mediciones, las figuras y los parámetros de la infección.